The Effect of Work Attitude, Organizational Climate and Training on Employee Performance in District Statistics Center Deli Serdang - Viny Arilia; Mhd. Dani Habra (International Journal of Economics (IJEC), 2022)
This research is a quantitative research can be defined as a research method based on the philosophy of positivism, used to research on a particular population or sample, data collection using research instruments. This study aims to determine the effect of work attitudes, organizational climate and training on employee performance at the Central Statistics Agency, Deli Serdang Regency. , Organizational Climate and Training on Employee Performance obtained tcount value of 2,349 > ttable 1,663 with a significant level of 0.000 <0.05. It can be concluded that the variables of Work Attitude, Organizational Climate and Training have a positive and significant effect on employee performance, so the second hypothesis (H4 ) is proven. The results of this study indicate that work attitudes, organizational climate and training have an influence on employee performance, that work attitudes, organizational climate, and training on employee performance are 82.3% while 17.7% are influenced by other variables outside this research and those not examined by the researcher.